PENGARUH TEKANAN ANGGARAN WAKTU, MOTIVASI DAN INTEGRITAS TERHADAP KUALITAS AUDIT: Studi Empiris pada Inspektorat Kota Ambon dan Inspektorat Provinsi Maluku - Christina Sososutiksno; Irene Intan Risakotta (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to determine the effect of time budget pressure, motivation and integrity on audit quality. The independent variables in this study are time budget pressure, motivation and integrity. The dependent variable in this study is audit quality. The data in this study are primary data obtained from distributing questionnaires directly to 27 auditors of the Ambon City Inspectorate and 22 Maluku Provincial Inspectorate auditors. The results of multiple linear regression research state that the time budget pressure variable has a negative effect on audit quality, while the motivation and integrity variables have a positive effect on audit quality